2016
DOI: 10.20884/1.anprod.2016.18.2.543
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Properties and Characteristics of Cow Milk Yogurt with Different Additional Fruit and Storage Time

Abstract: This research was aimed to evaluate the composition (total solids, water content, fat and protein), qualitative properties (color, aroma, and texture) and quantitative properties (free fatty acid and lactic acid) of cow milk yogurt with different fruits addition and storage time. Experimental method applied Completely Randomized Design with five treatments namely control, dragon fruit, mango, apple and banana (20% v/v), each with 5 replicates. Qualitative characteristic assessment was conducted on 0, 5, 10 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…The results of Oktavia et al, (2015) showed that storage of black mulberry yoghurt during distribution and marketing caused the increasing acidity of yoghurt (41). In contrast, Suriasih et al, (2014); Wulansari and Kusmayadi (2016) reported that yoghurt from blended cow and goat milk had higher nutrient content and easy digest than their milk (7,24). In another way, cow milk yoghurt adding different fruit increasing their benefit.…”
Section: Phmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of Oktavia et al, (2015) showed that storage of black mulberry yoghurt during distribution and marketing caused the increasing acidity of yoghurt (41). In contrast, Suriasih et al, (2014); Wulansari and Kusmayadi (2016) reported that yoghurt from blended cow and goat milk had higher nutrient content and easy digest than their milk (7,24). In another way, cow milk yoghurt adding different fruit increasing their benefit.…”
Section: Phmentioning
confidence: 98%
“…Yoghurt has a higher protein content than cow's milk and is low in fat. This is very useful for people increasing healthy in diet (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Yoğurtların kuru madde oranları arasındaki fark istatistiksel olarak önemli bulunmuştur (p<0.05). Wulansari ve Kusmayada [29]'nın farklı meyve ilaveli inek sütünden elde edilen yoğurtların sırasıyla ejder meyvesi, mango, elma ve muz katılan yoğurtlarda kuru madde sonuçlarını %13,628; %13,108; %14,376 ve %14,376 olarak bulmuşlardır. Tablo 1'de verildiği gibi yağ oranları K grubunda %3,38 ve A3 grubunda %3,21 olarak bulunmuş ve depolama süresince örneklerin yağ değerlerinde azalma görülmüştür.…”
Section: Bulgular Ve Tartışmaunclassified